Analisis Keterlambatan Pada Proyek Apartemen Berkonsep Transit Oriented Development (TOD) - Bagas Prawiro Dwiputranto; I Ketut Sucita (Politeknik Negeri Jakarta, 2020)
The problem in the The Conexio Cikunir 1 Apartment project which has the concept of Transit Oriented Development (TOD) was had delayed, which should have been 100% contractually completed, but only 46.231% have been realized. Based on these percentages, required an analysis of the dominant factors that causes of delayed in this project. This study has purpose to determine the dominant factor influencing the variables causing project delayed. Questionnaires were distributed to the respondents consisting of the contractors, owners and supervisory consultants involved in the apartment construction project. The results of the questionnaires were processed using SPSS 25 software. The data analysis method used is multiple linear regression method. The results of the research shows that factors which fulfilled on the partial test (t test) and has a significant influence is document of works variable (5.792 ) . This value has the highest rank of significance value for project delayed. Futhermore is planning & scheduling variable (2,805), equipments variable (2,482), managerial variable (2.324), materials variable (2,248), and external factors variable (2.094). The result of Adjusted R Square of 62.70% shows that the Factors that Causes of Delayed can affect the Project Delay variable by 62.70%, while the remaining 37.30% is affected by other variables not examined in this study.